Mecca and Main Street : Muslim life in America after 9/11 - Abdo, Geneive, 1960- (OUP E-Books., 2006)
Islam is America's fastest growing religion, with more than six million Muslims in the United States, all living in the shadow of 9/11. Who are our Muslim neighbors? What are their beliefs and desires? How are they coping with life under the War on Terror? In Mecca and Main Street, noted author and journalist Geneive Abdo offers illuminating answers to these questions. Gaining unprecedented access to Muslim communities in America, she traveled across the country, visiting schools, mosques, Islamic centers, radio stations, and homes. She reveals acommunity tired of being judged by Americans.